PENGARUH TEKNIK PERAWATAN PAYUDARA TERHADAP KELANCARAN PENGELUARAN ASI PADA IBU NIFAS: STUDI KASUS - Aeni, Cica Fikrotun; Purbaningsih, Endah Sari; Khoerunissa, Khoerunissa; Ulhaq, Dhiya; Triyani, Triyani; Komalasari, Siti (Coping: Community of Publishing in Nursing; Vol 10 No 4 (2022): Agustus 2022, 2022)
Preparation for breastfeeding a baby and its smoothness can be done with breast care or breast care, the breast is an organ in women that functions as a producer of breast milk, which is the staple food for newborns. Thus, breast care in the mother must be carried out from the beginning, namely from the time of pregnancy. This case study aims to identify the effectiveness of the application of breast care techniques on the smooth release of breast milk in postpartum mothers at Sumber Kasih Hospital, Cirebon City. This study uses case studies and literature reviews through Google Scholar. An article that reviews the application of breast care techniques to the smooth running of breast milk in post partum mothers. The keywords used to search the literature are breast care, breast care, postpartum mothers, postpartum mothers and the smooth production of breast milk with a span of the last 10 years, namely 2012-2022. The inclusion criteria set were: reporting research results regarding the application of breast care techniques. The exclusion criteria were related to medical therapy. In a total literature search, 13 articles were selected. Based on the 13 articles that were traced, there was an effectiveness in the application of breast care techniques to the smooth discharge of breast milk in postpartum mothers. It can be concluded that the application of breast care techniques to postpartum mothers is effective for smooth milk production so that post partum mothers can produce and provide breast milk to their babies.